Complete chloroplast genome sequence of Sphaerophysa salsula (Leguminosae). Issue 2 (1st February 2021) - Qu, Wen-Rui; Jiao, Pei-Pei; Jiang, Xi; Zhang, Shan-He; Yang, Tian-Ge; Li, Zhi-Jun; Wu, Zhi-Hua
Abstract: Sphaerophysa salsula (Pall.) DC. is a perennial herbaceous plant belonging to the genus Sphaerophysa, Galegeae, Leguminosae, and is mainly distributed in dry areas in Central Asia and Northwest China. The complete chloroplast genome with a total size of 123, 300 bp was reported in this study. Further annotation revealed the chloroplast genome contains 109 genes, including 76 protein coding genes, 29 tRNA genes, and four rRNA genes. A total of 107 simple sequence repeats (SSRs) from mononucleotide to hexa-nucleotide repeat motif were identified in the chloroplast genome. This information will be useful for study on the evolution and genetic diversity of Sphaerophysa salsula in the future.